(untitled) (Journal of Engineering, 2018)
This research is focusing on finding more effective polymers that leads to enhance the rheological properties of Water Base Muds. The experiments are done for different types of mud for all substances which are Polyacrylamide, Xanthan gum, CMC (Carboxyl Methyl Cellulose). This study shows the effect of add polymer to red bentonite mud, effect of add polymer to Iraqi bentonite mud, the effect of add bentonite to polymer mud. The mud properties of Iraqi bentonite blank are enhanced after adding the polymers to the blank mix, CMC gives the highest value of plastic viscosity and Gel strength than others; X-anthan gives the highest value of yield point and gel strength than others. For the red bentonite mud, Polyacrylamide has the highest shear stress and yield point than the others polymers, but Xanthan has the highest effect on plastic viscosity than other polymers. All polymers reduce filtration loss. The polymer solution mud failed to suspend the barite so we cannot use it as drilling fluid even so this mud has good Rheological properties (PV and YP). The maximum amount of each polymer is founded for the studied clay types.